The role of Branched Chain Amino Acids in the treatment of hepatic Encephalopathy - Dam, Gitte (J Clin Exp Hepatol, 2018)
The relationship between intake of nutrients and Hepatic Encephalopathy (HE) dates back to the historical roots of experimental hepatology. Branched-Chain Amino Acids (BCAA; Isoleucine, leucine and valine) have attracted particular interest and in 1956 Müting described the amino acid pattern in patients with cirrhosis. The abnormal plasma pattern has been characterized by the ratio between BCAA and aromatic amino acids in plasma, the so called 'Fischer´s ratio'. This ratio has been associated with the grade of HE. Under normal conditions, ammonia detoxification predominantly takes place in the liver. When the liver fails, the homeostasis is altered and muscle tissue becomes the main alternative organ for at least temporary detoxification of ammonia. BCAA are believed to support this muscle ammonia detoxification and the ammonia lowering effect of BCAA has been intensely investigated. In this review the effect of BCAA on muscle ammonia metabolism and the protein sparing and anabolic effects of BCAA are discussed. A Cochrane metaanalysis showed that BCAA had beneficial effects on HE with a number needed to treat of 5 patients (RR 0.73, 95% CI 0.61 to 0.88). The combined evidence suggests that although the pathophysiology is poorly understood, there is evidence to support clinical benefits of BCAA. BCAAs enhance muscle mass and exert anabolic effects via stimulation of protein synthesis. The beneficial long-term effects of BCAA on HE could be related to these effects and not only related to Branched-Chain Amino Acid increased ammonia metabolism.